2019
DOI: 10.1016/j.cmi.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Sera from different age cohorts in Belgium show limited cross-neutralization between the mumps vaccine and outbreak strains

Abstract: Objectives: Mumps used to affect children between 2 and 15 years old. The mumpsemeasleserubella (MMR) vaccine is available, with vaccine coverage rate of about 85% after two vaccine doses. Recently new mumps outbreaks have emerged in highly vaccinated populations; the causes for these new outbreaks are yet unknown. We tested if a difference in seroneutralizing capacity against the vaccine and wild-type viruses existed and if waning immunity could be detected. Methods: In this study, 570 serum samples (age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Reduced efficacy of vaccine-induced immunity against wild type MeV strains has been hypothesized to play a role in measles reemergence [11,38]. In the case of mumps, infection in fully vaccinated individuals are not uncommon, and serum samples from vaccinated individuals have been shown to neutralize the currently circulating mumps virus genotype G less efficiently than other genotypes and the vaccine strain [39,40]. Our study demonstrated that this is not the case for measles.…”
Section: Discussionmentioning
confidence: 59%
“…Reduced efficacy of vaccine-induced immunity against wild type MeV strains has been hypothesized to play a role in measles reemergence [11,38]. In the case of mumps, infection in fully vaccinated individuals are not uncommon, and serum samples from vaccinated individuals have been shown to neutralize the currently circulating mumps virus genotype G less efficiently than other genotypes and the vaccine strain [39,40]. Our study demonstrated that this is not the case for measles.…”
Section: Discussionmentioning
confidence: 59%
“…Cohen et al ( 101 ) also demonstrated minimal antibody level decline after two MMR doses 6–7 years after second vaccination. Neutralizing antibodies against the JL-5 vaccine strain has also been detected in ~80% for age groups 2–20 years, 67% for age group 24–26 years; and 77% for age group 50+ years ( 187 ).…”
Section: Factors Facilitating Current Mumps Outbreaks In Highly Vaccimentioning
confidence: 99%
“…Vaccination aims to stimulate the host immunological process and formation of cell-mediated immunological memory via the use of live-attenuated or of inactivated/subunit vaccine components to promote a cell-mediated immune response. Extensive knowledge gaps significantly hinder improvements to the mumps vaccine and prospects for mumps eradication and maintaining proficient population immunity ( 3 , 122 , 187 ). Few studies have collected data that examines different aspects of mumps immunity and are limited in their predictive value for future outbreaks ( 253 ).…”
Section: Laboratory Determinants Of An Effective Immune Response To Mmentioning
confidence: 99%
“…A previous study has shown that although neutralizing antibody titers were lower against some mumps virus strains than others, genetically diverse strains were neutralized in the sera obtained from children 6 weeks after the MMR vaccine administration [155]. Other studies conducted during mumps outbreaks have shown that the currently used genotype A vaccines provide suboptimal protection against genotype G, even if MMR vaccination was associated with less severe disease [37], and induce significantly lower neutralization titers against wild-type genotypes than against the vaccine strain [177,182]. Moreover, molecular evidence suggested that emergent mumps virus strains have different antigenic epitopes than vaccine strains [183].…”
Section: Vaccine Strains and New Genotypesmentioning
confidence: 98%
“…In many parts of the world, outbreaks have been attributed to different genotype variants (genotypes I, J, F, G, C, H, K) as compared to the vaccine strains [26,37,107,155,[171][172][173][174][175][176][177][178][179][180][181]. In particular, recent outbreaks of mumps caused by the genotype G virus have been reported in several countries, such as the USA, Canada, Norway, Scotland, and Belgium [37,155,[177][178][179][180][181]. While differences between vaccine and circulating strains may induce vaccine escape and favor outbreaks, the major cause of mumps outbreaks seems to be the waning immunity after vaccination and contradicting literature exists as to the importance of the mumps genetic variants [107,155].…”
Section: Vaccine Strains and New Genotypesmentioning
confidence: 99%